EVALUASI SISTEM PENGENDALIAN INTERN PINJAMAN KREDIT PADA KOPERASI KARYAWAN SARANA ABADI SEJAHTERA DI SAMARINDA - Adi Suroso., Rineke Ernawati Mananeke, H. Eddy Soegiato K (EKONOMIA, 2015)
The aim of this study was to evaluate the internal control system of credit loans in the Cooperative Employees who should be a concern cooperative management and coaching. The study was conducted by comparing the internal control system applicable to cooperative with the theory of the internal control system. Data collection techniques used were interviews, questionnaires, observation, and research directly to the object. Based on the results of a study of internal control loans to cooperative employees Sarana Abadi Sejahtera, using a questionnaire which refers to the internal control framework of COSO on the elements of internal control. The test results showed that of the elements of internal control according to the framework of COSO, elements of the control environment, determination of risk, control activities, information and communication and monitoring is not effective, it was found that part of the credit function into one with operational functions, the cashier took home cash because absence brangkas storage of cash, cooperative management inactive, absence of internal audit and audit impromptu especially in the field of finances, the forms of credit and proof of cash entering or proof of cash out no serial number printed on the cooperative does not have special sections credit analysis , In addition to the loan application procedure of credit disbursement in the cooperative is ineffective because it does not comply with the procedures that exist in theory.